Sectoral Ego Versus Collaboration: Comparing The Regulatory and Institutional Foundations of Digital Transformation In Balikpapan City and Samarinda City - Paisal Akbar; Achmad Nurmandi; Dyah Mutiarin; Hasse Jubba; Zuly Qodir; Pande Made Kutanegara; Bambang Irawan (Universitas Muhammadiyah Makassar, 2025)
This study critically examines the foundational readiness for digital government transformation by comparing the regulatory and institutional capacities of two major cities in East Kalimantan, Indonesia: Kota Balikpapan and Kota Samarinda. Using a qualitative comparative case study, data were gathered from in-depth document analysis, surveys of eight local government officials, and semi-structured interviews with eight key informants from the Communication and Information Offices. The findings reveal a stark divergence in institutional execution despite similar regulatory frameworks. Kota Balikpapan’s strong technical regulations are hindered by pervasive sectoral ego (reported by all respondents), creating implementation friction. In contrast, Kota Samarinda exhibits a collaborative institutional culture with no inter-agency resistance, driven by its integrative “Smart City Plus” vision and a centralized service platform. The study concludes that mature digital government depends less on regulatory completeness and more on deliberate governance engineering, intentional design of collaborative structures, leadership as integrators, and trust-based operational cultures. This research contributes by asserting that in decentralized contexts, the sociopolitical dynamics of local bureaucracy are the ultimate determinants of success, outweighing technology alone.